EDUCATION SYSTEM OF THE REPUBLIC OF UZBEKISTAN. REFORMS IN EDUCATION. TYPES OF EDUCATIONAL INSTITUTIONS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This abstract discusses the recent education system reforms in Uzbekistan aimed at modernizing and enhancing the quality of education across various levels. The reforms include updating curricula to align with global standards, improving teacher training programs, promoting digital literacy through educational technology integration, expanding access to education in rural areas, and strengthening quality assurance mechanisms. The diverse types of educational institutions in Uzbekistan, ranging from general education schools to specialized institutions and universities, play crucial roles in delivering quality education and preparing students for diverse career paths. These reforms signify Uzbekistan's commitment to nurturing a skilled workforce and fostering lifelong learning opportunities, ultimately contributing to the country's socioeconomic development and global competitiveness.